Pengaruh Kinerja ESG, Green Innovation, dan Struktur Modal Terhadap Nilai Perusahaan: Peran Mediasi Kinerja Keuangan: Studi Empiris pada Perusahaan yang Terdaftar di Indeks Kompas 100 Periode 2020-2022 - Siti Haisyah; Giriati; Wendy (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Currently, attention to sustainable development is increasing along with global awareness of environmentally responsible business practices. The application of these sustainability principles drives changes in corporate business practices, which focus on managing environmental, social, and governance aspects, as well as green innovation to support the long-term sustainability of the company. This study analyzes the effect of ESG performance, green innovation, and capital structure on firm value with financial performance as a mediating variable. The study population is companies listed on the Kompas 100 Index for the period 2020–2022, using panel data regression and the Sobel test. The results show that ESG performance and green innovation have a positive and significant effect on financial performance, but are not significant on firm value. Capital structure has a negative effect on financial performance, but has a positive and significant effect on firm value. Financial performance has a positive and significant effect on firm value, but does not mediate the relationship between ESG performance, green innovation and capital structure, on firm value.